The evaluation of three electronic apex locators in teeth with simulated incomplete oblique root fractures - Lotika Beri; Gaurang Matariya (Wolters Kluwer Medknow Publications, 2009)
Traumatic injuries to the tooth may lead to a dilemma in the treatment plan specially in teeth with fractured roots with displacement. The treatment plan for teeth with root fractured with displaced apical segment is to implement root canal therapy up to the fractured line leaving the apical segment untreated. Determining the working length of the coronal segment may be difficult by radiograph, so we tested the accuracy of three electronic apex locators (EALs) to locate the apical limit in teeth with simulated oblique root fractures. An oblique incomplete root fracture was simulated on 15 freshly extracted maxillary anterior teeth by means of a notch made on the vestibular root plane 8 mm from the anatomic apex. The EALs investigated were the ProPex (Dentsply Maillefer, Ballaigues, Switzerland), Root ZX (J.Morita Co, Kyoto, Japan). Dentaport ZX ( J. Morita Co., Kyoto, Japan). The electronic measurements were compared with the real "working length." The accuracy obtained was of 86.6% (n _ 13) with Root ZX , 66.6% (n _ 10) with the ProPex, and 60% (n _ 09) with Dentaport ZX. When tolerances of 0.5-mm and 1.0-mm tolerance were, respectively, allowed. The analysis of variance (p _ 0.05) and chi-square test (0.5 mm/p _ 0.47 and 1.0 mm/p _ 0.63 tolerances) showed no statistical significant differences between the EALs at either tolerance level.